Studies in Historical Linguistics in Honor of George Sherman Lane Festschrift for George S. Lane - Arndt, Walter W.; Brosman, Paul W. Jr; Coenen, Frederic E.; Friedrich, Werner P. (UNC Studies in the Germanic Languages and Literatures, 1967)
This 1967 volume honoring Professor George S. Lane also features eight of his articles on aspects of Tocharian that made him a supreme authority in his field. The essays that follow by Cowgill, Eliason, Haas, Hahn, Hamp, Lehmann, Reitz, Robinson, Watkins, and Widding range from studies of Old Norse and Old English to Hittite.